2014
DOI: 10.1186/2052-1839-14-13
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and associated factors among school-age children in Filtu Town, Somali region, Southeast Ethiopia

Abstract: BackgroundAnemia is one of the major public health problems affecting more than half of school-age children in developing countries. Anemia among children has been conclusively seen to delay psychomotor development, poor cognitive performance, impaired immunity and decrease working capacity. The purpose of this study is to determine the prevalence and associated factors of anemia among school-age children in Filtu Town, Somali region, Southeast Ethiopia.MethodsA community based cross-sectional study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
50
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 14 publications
13
50
5
4
Order By: Relevance
“…12 Other studies done by Sudhagandhi et al, and Bekele et al, found that the prevalence of anemia was higher in females. 9,13 Socioeconomic Status: present study showed that incidence of anemia was high in class IV (upper lower) children (26.3%) followed by class III (lower middle) children (19.6%) and class II (upper middle) children (13.5%). Similar finding was recorded by Jain et al, in a study done in Uttarakhand which showed that anemia was more common in lower socio-economic class (90.6%) and 37.5% in class III and Class II.…”
Section: Sexmentioning
confidence: 51%
See 3 more Smart Citations
“…12 Other studies done by Sudhagandhi et al, and Bekele et al, found that the prevalence of anemia was higher in females. 9,13 Socioeconomic Status: present study showed that incidence of anemia was high in class IV (upper lower) children (26.3%) followed by class III (lower middle) children (19.6%) and class II (upper middle) children (13.5%). Similar finding was recorded by Jain et al, in a study done in Uttarakhand which showed that anemia was more common in lower socio-economic class (90.6%) and 37.5% in class III and Class II.…”
Section: Sexmentioning
confidence: 51%
“…Children which belonged to 5 to <12 years were 237 (43.1%) and ≥12 to <15 years were 313(56.9%) 52.9% were males and 47.1% were females. The overall prevalence of anemia in the study group (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) years is 20.7% (114), of which the prevalence in 6 to <12 years age group was 23.6% (56) and ≥12 to <15-year age group was 18.5% (58). There was no significant difference between both the age group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, families with high income levels will be better able to provide for their daily needs, including the need for food, whereas with a low monthly household income the possibility of a child and other family members not getting food rich in sufficient iron and the diet of children living in families with less economics are usually monotonic (Gutema, 2014). …”
Section: Discussionmentioning
confidence: 99%